Headmaster's decision making in efforts to improve teacher’s digital literacy competencies in junior high school - Intan Maurissa; Teguh Trianung (Institute of Computer Science (IOCS), 2023)
This article aims to: find out the art of decision-making by The Headmaster in an effort to foster digital literacy competencies. This research is a qualitative study with Focus Group Discussion (FGD) interviews involving The Headmaster directly and the responsibility bearers in the school framework totaling 5 people including the deputy head of curriculum, vice Headmaster, and other teachers who seek to explore and narrate the reality of digital literacy implementation in junior high schools. Based on the results of the study, it is known that The Headmaster's decision-making in efforts to foster teachers' digital literacy competencies is considered not responsive and has not fully achieved significant results due to several obstacles such as the economic background of students, the lack of training and technical resources, and the lack of facilities and infrastructure owned by the school.